EFFICIENCY OF A BIOL MADE FROM HARVEST RESIDUES IN THE PRODUCTION OF COCOA (Theobroma cacao L.), CLONE TSH 565 IN AN ORGANIC AGROFORESTRY PLANTATION - LUCANO-LOPEZ, Diana (2023)
The quality and efficiency of a biol made from cocoa harvest residues on a fine aroma cocoa clone (TSH-565) was evaluated in an agroforestry plot located in the district of Campo Verde, Ucayali region. A randomized complete block design was used with three replications and five treatments applied at the canopy level. The control treatment consisted of a unique application of the fertilization made by the producer of 1 kg of poultry manure, 250 g of phosphate rock and 250 g of dolomite, T1 in the application of biol diluted in water at a concentration of 10%, T2 at 15%, T3 at 20% and for T4, biol at 15% was combined with the addition of the fertilization made by the producer. The biol prepared has a high nutritional content of macro and micronutrients (N, P, K, Ca, Mg), salinity and humins. The N and K content in the soil did not evidence considerable variation between treatments, except for P, where increases were observed. During the dry season, only weight, diameter (T1 and T2) and number of cocoa pods (T4 and T2) were significantly higher (P<0.05). With the onset of rains, no significant residual effects were observed. The highest yields for dry grain were obtained in T1 (366 kg ha-1) and T2 (380 kg ha-1), the lowest being the control with 185 kg ha-1 respectively.